Analisis Persepsi Pengguna Aplikasi Transportasi Grab terhadap Perilaku Menggunakan Alat pembayaran OVO - Katarina Siena; Aurelia Melinda Nisita Wardhani (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2020)
OVO Mobile Payment is a new method of online payment which has existed and cooperated together with Grab since June 2018. This research aims to understand user's perception on Grab transportation application towards usage behavior of OVO mobile payment. The type of this research is a survey study. The research subjects are all users of OVO mobile payment who use online transportation in Jabodetabek and Yogyakarta. Sampling was collected using snowball method. The data was collected through a survey method by spreading online questionnaires and online interviews through Google Form. The result shows that user's perception of OVO mobile payment has an effect towards user's behavior. Those are caused by seamless coverage, trust, safety, and privacy of users when they use the OVO mobile payment in Grab application.